2013
DOI: 10.1093/jnci/djt352
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Alkylresorcinols, Biomarkers of Whole-Grain Wheat and Rye Intake, and Incidence of Colorectal Cancer

Abstract: BackgroundFew studies have investigated the association between whole-grain intake and colorectal cancer. Because whole-grain intake estimation might be prone to measurement errors, more objective measures (eg, biomarkers) could assist in investigating such associations.MethodsThe association between alkylresorcinols, biomarkers of whole-grain rye and wheat intake, and colorectal cancer incidence were investigated using prediagnostic plasma samples from colorectal cancer case patients and matched control subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…Observational studies in free-living adults have only recently begun to include measures of plasma AR concentrations as independent biomarkers for assessing wholegrain exposure (18)(19)(20)32) . In a small sample of 241 older community-dwelling adults, plasma AR concentrations were inversely associated with BMI (20) , confirming a previously observed inverse relationship between whole-grain intake and BMI (33) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies in free-living adults have only recently begun to include measures of plasma AR concentrations as independent biomarkers for assessing wholegrain exposure (18)(19)(20)32) . In a small sample of 241 older community-dwelling adults, plasma AR concentrations were inversely associated with BMI (20) , confirming a previously observed inverse relationship between whole-grain intake and BMI (33) .…”
Section: Discussionmentioning
confidence: 99%
“…To date, few observational studies have used plasma AR as independent biomarkers of whole-grain intake to confirm observed associations between intake and disease outcomes (18)(19)(20) . The main advantage of using an independent biomarker of food intake to determine dietdisease associations in observational studies is that they are independent of subjective errors in reporting dietary intake (21) .…”
mentioning
confidence: 99%
“…Four observational studies [69,[92][93][94] were included in analysis of the association of ARs intake with cancer risk, among which two studies [92,93] involved colorectal cancer. One study dealt with prostate cancer [69] and one study [94] with endometrial cancer (Table 1).…”
Section: Prospective Studiesmentioning
confidence: 99%
“…One study dealt with prostate cancer [69] and one study [94] with endometrial cancer (Table 1). The first study on colorectal cancer included a large, multicenter cohort with more than one million individuals from 10 European countries [92]. Total plasma concentration defined as a sum of plasma AR homologues C17:0, C19:0, C21:0, C23:0, and C25:0 was analyzed in matched case-control pairs.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Alkylresorcinols (ARs) are a group of phenolic lipids present in the outer layer of mainly whole grain rye and whole grain wheat (>500 μg/g) [6]. High concentrations of plasma ARs were associated with a lower incidence of distal colon cancer [8].…”
Section: Introductionmentioning
confidence: 99%